Prevalence, associated risk factors and antimicrobial susceptibility patterns of Shigella infections among diarrheic pediatric population attending at Gondar town healthcare institutions, Northwest Ethiopia - Amare Alemu; Mekuanint Geta; Selomon Taye; Setegn Eshetie; Tigist Engda (Tropical Diseases, Travel Medicine and Vaccines, 2019)
Abstract Background Diarrhea caused by Shigella species remains a major public health threat especially in the pediatric population. A regular surveillance system needs to be in place, in order to explore the burden, antimicrobial resistance patterns and associated risk factors for Shigella infections. Therefore, the aim of this study was to assess the prevalence, antimicrobial susceptibility patterns and associated risk factors of Shigella infections among diarrheic pediatric population attending at selected healthcare institutions in Gondar town. Methods A cross-sectional study was conducted in Gondar town healthcare institutions from January to March 2018. A simple random sampling technique was used to enroll 272 study participants. Structured questionnaires were used to gather socio-demographic, environmental and associated risk factors data. Stool samples were collected from diarrheic pediatric patients and inoculated onto MacConkey media, salmonella-shigella agar, and xylose-lysine deoxy-cholate agar. Identification of the bacterial species was carried out by using biochemical tests. The disc-diffusion method was used to determine the antimicrobial susceptibility of the isolates by standardizing the bacterial suspension with a 0.5 McFarland solution. A statistical analysis was done using SPSS version 20 statistical package and P-value < 0.05 was considered as statistically significant. Results From the total study participants, 29(10.7%) of the patients were culture positive for Shigella species. The habit of eating raw food and nutritional status of children were statistically significant with shigellosis (p < 0.05). Shigella species were found highly resistant to amoxicillin and tetracycline but susceptible to nitrofurantoin and norfloxacin. Conclusion High prevalence of Shigella species were detected in this study. Through in-vitro drug susceptibility testing, norfloxacin and nitrofurantoin were found to be effective against the isolates, while high resistance rates were observed for tetracycline, and amoxicillin. The findings highlighted the need for regular drug resistance information for the best management of infections.